INTERRELASI BESI DENGAN SITOKIN DAN VICE VERSA - Suega, Ketut (journal of internal medicine; Vol. 13, No. 1 Januari 2012, 2014)
Iron is an essential substance needed for metabolism process, such as for transporting oxygen to the tissues for energy production in cells. Iron is also important for transporting electrons in the mitochondria for cell respiration process, and for synthesizing Deoxyribo Nucleic Acid (DNA). In addition to its role in oxygen transport and metabolic pathways, iron plays a pivotal role in immune function by promoting lymphocyte activation and proliferation. On the other hand, iron over-load can have immune disorders and yet pathogenic microorganism require iron for their growth and proliferation. Therefore iron homeostasis must be maintained through careful regulation of duodenal absorption and recycling of iron stores since human body has no ideal excretory system for iron. Discovery of hepcidin peptide help clarify molecular based of cellular interaction between duodenal iron absorption capacity and iron stores cells. Hepcidin a putative negative humoral regulator of iron homeostasis by inhibiting iron absorption and couple with ferroportin preventing iron exported from intracellular iron stores. Hepatic hepcidin expression is increased in iron overload and decreased in iron deciency. In addition to regulation by body iron needs, hepcidin is increased during an acute phase respone of inlammation processed. When an in!ammation is initiated, liberation of proin!ammatory cytokine IL-6 stimulate hepcidin expression causing iron absorption and iron release from the macrophage of the reticuloendotheleal system are decreased. Many other studies on humans and experimental animals have shown signicant change of the levels of certain cytokines in iron deciency state such as IL-2; IL-4; IL-6; IL-10; IL-12; IFN gamma. As summarized, cytokines in!uence iron homeostasis and in the other way iron in!uences activity of cytokines and immune effector mechanism of macrophages, and all these affect the level of immune defence against invading pathogens.
Keywords: Iron, cytokine, immune respone, hepcidin.